Análise numérica de risco climático de ocorrência de requeima na cultura da batata na região central do Rio Grande do Sul - Radons, Sidinei Zwick (2012)
Diseases and environment are closely related, especially with regard to air temperature and relative humidity. The weather data tend to follow a daily pattern of temporal variation, which derives mainly from the daily variation of the surface radiation balance. Based on this, this study aimed to make a qualitative and quantitative description of the database of the Automatic Meteorological Station of the Instituto Nacional de Meteorologia (INMET) in Santa Maria, RS, determine the hours of greatest frequency of occurrence of daily extreme air temperatures in Santa Maria, develop models to estimate hourly values of air temperature (T) and relative humidity (RH), based on values measured in "UTC standard times" and on the daily minimum air temperature and to determine the risk of fungal diseases occurrence during the developmental cycle of potato in different planting dates, using the Blitecast forecasting system. Models were fitted to estimate air T and partial vapor pressure of water at different times of the day. RH was indirectly obtained from partial vapor pressure of water and saturation vapor pressure, calculated from estimated T values. The database of Principal Climatological Station of Santa Maria was transformed to an hourly estimated T and RH database and the Blitecast's calculated severity values (CSV) were obtained for 14 planting dates in 43 years. The automatic weather station of Santa Maria, RS, belonging to INMET, shows 90.1% of the days of flawless data records in 10 years, from 2002 to 2011. The minimum daily air temperature in Santa Maria occurs more frequently at 09AM UTC, corresponding to 6AM on local official time, from September to February. From March through August, this time is delayed, and its occurrence to be more frequent at 10 h UTC. The precision of the estimates ranged from 0.7 ºC to 1.5 ºC, with average deviation of 0.65 °C for T and 0.7 % to 1.2 %, with average deviation of up to 4% for RH depending on the time. Potato crops during the Fall growing season require on average 54% more fungicide applications compared to the Spring season. In the Spring growing season the most probable number of sprayings ranged from two to four and from six to seven in the Fall growing season. Potato crops planted in August and March were demanded a lower economic, ecological and farmer health cost in crop protection against late blight than earlier crops (July and February).